Genetic Characterization of Highly Pathogenic Avian Influenza (H5N8) Virus from Domestic Ducks, England, November 2014 - Amanda Hanna; Jill Banks; Denise A. Marston; Richard J. Ellis; Sharon M. Brookes; Ian H. Brown (Emerging Infectious Diseases, 2015)
Genetic sequences of a highly pathogenic avian influenza (H5N8) virus in England have high homology to those detected in mainland Europe and Asia during 2014. Genetic characterization suggests this virus is an avian-adapted virus without specific affinity for zoonoses. Spatio-temporal detections of H5N8 imply a role for wild birds in virus spread.